Chapter Bibliography (Manchester University Press, 2014)
Recent decades have witnessed profound shifts in the politics of medicine and the biological sciences. Members of several professions, including philosophers, lawyers and social scientists, now discuss and help regulate issues that were once left to doctors and scientists, in a form of outside involvement known as 'bioethics'. The making of British bioethics provides the first in-depth study of the growing demand for this outside involvement in Britain, where bioethicists have become renowned and influential 'ethics experts'. The book moves beyond existing histories, which often claim that bioethics arose in response to questions surrounding new procedures such as in vitro fertilisation. It shows instead that British bioethics emerged thanks to a dynamic interplay between changing sociopolitical concerns and the aims of specific professional groups and individuals. Highlighting this interplay has important implications for our understanding of how issues such as embryo experiments, animal research and assisted dying became high profile 'bioethical' concerns in late twentieth century Britain. And it also helps us appreciate how various individuals and groups intervened in and helped create the demand for bioethics, playing a major role in their transformation into 'ethics experts'. The making of British bioethics draws on a wide range of materials, including government archives, popular sources, professional journals, and original interviews with bioethicists and politicians. It is clearly written and will appeal to historians of medicine and science, general historians, bioethicists, and anyone interested in what the emergence of bioethics means for our notions of health, illness and morality.
Wellcome Trust
English
Keywords: History of medicine; bioethics; ethics; history of medicine; history of science; theology